التحليل المكاني للتوزيع الجغرافي لمصانع معالجة وتعبئة مياه الشرب في بلدية مصراتة: دراسة جغرافية (Journal of Academic Research, 2025)
AbstractThe study aimed to show the geographic distribution of drinking water treatment and bottling plants in the municipality of Misrata and to determine their spatial distribution pattern using some spatial analysis tools provided by geographic information systems technology, such as the ideal and actual mean center, standard distance and distribution direction, service range, proximity coefficient, Moran's association coefficient, Kernel analysis, and spatial allocation analysis, and plotting them on digital maps.  The study used a number of approaches, such as the descriptive approach to describe the phenomenon under study and the quantitative approach to analyze the statistical aspects related to the subject of the study. Several results were reached, including: that the distribution pattern of drinking water treatment and bottling plants in general tends to be scattered and spread across the northern and eastern parts of the study area, spread   between the second and fourth ring roads and the areas following the fourth ring road. The application of the analysis of the service coverage of water treatment and bottling plants also showed that there is an overlap in the service coverage between 35 out of 52 plants, at a rate of 0.50%